The Effect of Fe y Alegria on School Achievement: Exploiting a School Lottery Selection as a Natural Experiment - Pablo Lavado; Santiago Cueto; Gustavo Yamada; Micaela Wensjoe (Institute of Labor Economics (IZA), 2016)
Fe y Alegria is an organization working in many developing countries as a public-private partnership. This study estimates the effect of one Fe y Alegria school in Peru on mathematics and reading comprehension among second grade primary pupils, between 2007 and 2012. The identification strategy is based on the fact that for this school Fe y Alegría conducted a lottery to determine which students would be accepted onto first grade. We could prepare our estimates only for one school where records for several years were available. The results show that this Fe y Alegria school generated substantial score gains for lottery winners, equivalent to 0.4 standard deviations. We also found that this effect has been increasing over time. In reading comprehension the effect was 0.17 s.d. in 2007 and 1.02 s.d. in 2012. In math, the effect was 0.29 s.d. in 2007 and 1.2 in 2012. These are promising results in a country where overall student achievement in standardized tests has been low, and where discussions on under what conditions may public partnerships result in better educational outcomes.
Keywords: C13; C33; C93; I21; I22; 330; education; public-private partnerships; quality education; Fe y Alegría; math performance; private school; reading comprehension performance